A relação entre o modelo Zona Franca em Manaus-AM e as questões climáticas: período de 1958 a 2017 - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The general objective of this work was to analyze the influence of the Free Zone and its consequences on Manaus climate from the characteristics of the climatic elements (rainfall and air temperature) from 1958 to 2017. Secondary precipitation and temperature data were collected. from 1958 to 2017 from INMET / BDMEP, from the IBGE Statistical Yearbook from 1959 to 1961 and dissertation from Aguiar (1995); IBGE population data from 1950 to 2010 and 2017 estimates and INPE satellite images from 1972 to 2017, which were submitted to temporal and statistical analysis. The results showed that the annual precipitation totals had many oscillations during the data series, where it was possible to observe years when the accumulated totals did not reach 2000 mm annual and years that the totals exceeded 3000 mm annual. The Mann-Kendall test did not identify significant trend for annual and monthly totals. The relationship analysis with the Pacific TSM indicated moderate negative relation (r = -0,58), the relation with the expansion of the urban area indicated moderate negative relation (r = 0.46), but without significance. The Mann-Kendall test showed a negative trend, ie a reduction in the number of annual rainy days over the time series (Z = -2,39). The relationship analysis with the TSM identified weak negative relation (r = -0,37) and with the expansion of the urban area, the coefficient pointed weak negative relation (r = -0,12) without significance. The most significant results corresponded to the historical series of average compensated temperature, maximum average and minimum annual average. The Mann-Kendall test showed quite significant positive trends for both the annual averages (compensated, maximum and minimum) (Z > 4,0) and the monthly averages (Z > 2,0), ie, increase in temperatures in the 60 years of data. Correlation analyzes with the TSM did not identify significant relationship for any of the temperatures. However, correlation analyzes between temperatures and urban sprawl showed a strong positive relationship with significance for mean maximum temperatures (r = 0,83). It is recommended to tackle and continue increasingly in-depth climate studies that can more accurately and consistently answer the issues attributed to the still quite complex climate of the Amazon region.
The relationship between the free zone model in Manaus-AM and the climatic issues: period from 1958 to 2017.
Keywords: Precipitação (Meteorologia) - Manaus (AM) - 1958-2017; Planejamento urbano - Fatores climáticos - Manaus (AM) - 1958-2017; Mudanças climáticas - Manaus (AM) - 1958-2017; CIENCIAS HUMANAS: GEOGRAFIA; Manaus; Precipitação; Temperatura